Determinant Earnings Quality, Size of Companies Registered In Indonesia, Malaysia, America and Singapore - Alfarisy Rahersya, Revan; Daito, Apollo (Devotion : Journal of Research and Community Service, 2022)
The industrial revolution 4.0 at this time requires companies to interact directly with the global market. The intense global competition we are facing includes the economic sector which is growing rapidly accompanied by technological developments. The purpose of this research is to examine the influence of the factors that influence earnings quality. the data analysis technique used in this study is multiple linear regression analysis. The population in this study are companies listed on the Indonesia Stock Exchange, the Kuala Lumpur Stock Exchange, the United States Stock Exchange and the Singapore Stock Exchange. Data collection used a purposive sampling method, with a total sample of 52 with a quota of 13 samples for each country. The independent variables of this study are Leverage and Profitability, the dependent variable of this study is Earnings Quality. The results showed that the Leverage and Profitability variables had no effect on earnings quality in all categories of this study, while Size Companies were able to moderate the effect on earnings quality in Indonesia and Malaysia.